Does openness to international financial flows contribute to productivity growth? - M. Ayhan Kose; Eswar S. Prasad; Marco E. Terrones (Institute for the Study of Labor (IZA), 2008)
Economic theory has identified a number of channels through which openness to international financial flows could raise productivity growth. However, while there is a vast empirical literature analyzing the impact of financial openness on output growth, far less attention has been paid to its effects on productivity growth. This paper provides a comprehensive analysis of the relationship between financial openness and total factor productivity (TFP) growth using an extensive dataset that includes various measures of productivity and financial openness for a large sample of countries. We find that de jure capital account openness has a robust positive effect on TFP growth. The effect of de facto financial integration on TFP growth is less clear, but this masks an important and novel result. We find strong evidence that FDI and portfolio equity liabilities boost TFP growth while external debt is actually negatively correlated with TFP growth. The negative relationship between external debt liabilities and TFP growth is attenuated in economies with higher levels of financial development and better institutions.
urn:nbn:de:101:1-20080820190
Keywords: F41; 330; Financial openness; capital account liberalization; capital flows; external assets and liabilities; foreign direct investment; portfolio equity; debt; total factor productivity; Kapitalmarktliberalisierung; Kapitalmobilität; Produktivität; Wirtschaftswachstum; Direktinvestition; Portfolio-Investition; Auslandsverschuldung; Welt